Test system for the visualization of dynamic disasters and its application to coal and gas outburst. (October 2019) - Zhou, Bin; Xu, Jiang; Peng, Shoujian; Geng, Jiabo; Yan, Fazhi
Abstract: With increasing depths of mines, complex, sudden, and devastating coal and gas outburst become more frequent; however, the precise mechanisms of these disasters remain unknown. To study the mechanisms of coal and gas outburst further and understand the processes that lead to these dynamic disasters, a novel complete testing system for the visualization of such disasters was designed. The testing system mainly includes a power system and a simulated roadway system. The power system consists of loading and control parts, a specimen chamber, a bearing frame and base, and other attachments. The simulated roadway system consists of a pressure relief device, straight roadways, cross roadways, a gradient section, and a visualization and image acquisition subsystem. Using this test system, the evolution of spatiotemporal characteristics of several physical fields in coal seams and roadways during realistic coal and gas outburst process were obtained in the laboratory for the first time. The results of this study are significant in the research of coal and gas outburst mechanisms and prediction of outburst.